Predicting environmental gradients with fern species composition in Brazilian Amazonia - Gabriela Zuquim; Hanna Tuomisto; Mirkka M. Jones; Jefferson Prado; Fernando O.G. Figueiredo; Gabriel M. Moulatlet; Flavia R.C. Costa; Carlos A. Quesada; Thaise Emilio (WILEY-BLACKWELL, 2022)
Conclusions: Fern species composition can be used as an indicator of soil cation concentration, which can be expected to be relevant also for other components of rain forests. Presence-absence data are adequate for this purpose, which makes the collecting of additional data potentially very rapid. Comparison with earlier studies suggests that edaphic preferences of fern species have good transferability across geographical regions within lowland Amazonia. Therefore, species and environmental data sets already available in the Amazon region represent a good starting point for generating better environmental and floristic maps for conservation planning.